Effects of War and Armed Conflict on Adolescents’ Psychopathology and Well-Being: Measuring Political Life Events among Youth - Slone, Michelle (Terrorism and political violence, 2022)
Although research on the consequences of war exposure on children’s mental health has made significant progress in the past decades, a lack of valid measures for quantifying the incidence, severity and variability of exposure can hamper identification of at-risk children and mental health delivery in conflict-affected areas. The present study investigated the psychometric properties of a new political life events scale for youth (PLE-Y) that comprehensively assesses personal political violence exposure history. The PLE-Y was administered to 6,254 adolescents aged twelve to eighteen in two large samples in a region in Israel that has been characterized by high exposure to political violence. Adolescents were assessed for political life events exposure, psychiatric symptoms, emotional and behavioral problems, and subjective well-being. Exploratory and confirmatory factor analyses supported a two-factor structure of the PLE-Y (severe and mild), representing the severity levels of exposure. Results confirmed positive relations between severity of PLE exposure and psychiatric symptoms, emotional and behavioral difficulties, and lower subjective well-being. This study demonstrated the importance of taking into account the personal political violence exposure history and the subjective interpretations of impact of the events to accurately identify the mental health risks to youth who are chronically exposed to protracted political violence.